In their parents' voices : reflections on raising transracial adoptees - Simon, Rita J. (Rita James), 1931-2013 (Columbia University Press, 2007)
Rita J. Simon and Rhonda M. Roorda's In Their Own Voices: Transracial Adoptees Tell Their Stories shared the experiences of twenty-four black and biracial children who had been adopted into white families. The book has since become a standard resource for families and practitioners. Now, in this sequel, we hear from the parents of these remarkable families and learn what it was like for them to raise children across racial and cultural lines. Simon and Roorda's candid interviews shed light on the issues these parents encountered while raising their children and reveal whether t.